Japan in world history - Huffman, James L. (New Oxford world history, 2010)
"Here is a marvelous compact history of Japan from earliest times to the present focusing on Japan's relationships with the rest of the world. In lively prose rooted in observations by people who lived the history, the work highlights the contributions of a wide range of acetors: women as well as men, commoners as well as elites"--Publisher supplied summary.